America is not all traffic lights : poems of the Midwest - Fleming, Alice Mulcahey 1928- (Boston : Little, Brown, 1976)
An anthology of poems reflecting the ambience of the Midwest through such voices as William Rose Benét, Carl Sandburg, and Sherwood Anderson.
Keywords: American poetry -- Collections; Middle West -- Description and travel -- Juvenile poetry; Middle West -- Poetry